The day is dark - Yrsa Sigurðardóttir (Minotaur Books/Thomas Dunne Books, 2013)
When all contact is lost with two Icelanders working in a harsh and sparsely populated area on the northeast coast of Greenland, Thóra is hired to investigate. Is there any connection with the disappearance of a woman from the site some months earlier? And why are the locals so hostile?